Implementasi dan tantangan kurikulum merdeka dalam mendukung tujuan pendidikan nasional I MTS Al-Khairiyah Tanjung Priok - Hardjadinata Hardjadinata; Kamil Mukhtar; Muhammad Fery Mustika; Marhamah Marhamah; Popi Puadah (SAP (Susunan Artikel Pendidikan), 2025)
The purpose of this study is to look into how the Independent Curriculum is being used and what problems it is encountering in order to help reach national education goals in the Fiqh subject at MTs Al-Khairiyah Tanjung Priok. The Independent Curriculum is designed to provide flexibility in the learning process by emphasizing character development, strengthening competencies, and empowering students' potential holistically. Despite facing various obstacles, the implementation of the Independent Curriculum in the Fiqh subject has made a positive contribution in shaping students' religious attitudes and characters in accordance with national education goals. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. The purpose of this study is to optimize learning outcomes. With an integrated approach, the Independent Curriculum can be a strategic foundation in developing character-based and contextual education.